Analysis Of Pending Claims For Inpatients Social Security Organizing Body (Bpjs) Health Hospital Mitra Siaga Tegal: Analisis Pending Klaim Pasien Rawat Inap Badan Penyelenggara Jaminan Sosial (Bpjs) Kesehatan Rumah Sakit Mitra Siaga Tegal - Indira, Zahrasita Nur; Yustafia, Atiqah Filda; Wijayanti, Wahyu Nur; Bella, Cindy Rozza; Mulyani, Agustina Dwi; Wibowo, Dimas Ari (Procedia of Engineering and Life Science, 2025)
The Hospital understands and realizes the importance of the claim process as a reimbursement for insurance patients who have been treated. pending claims, namely the return of claims where there is no agreement between BpJS Health and FKRTL regarding coding and medical rules (dispute claims), but settlements are carried out in accordance with statutory provisions. Mitra Siaga Tegal Hospital in September 2022 obtained data that there were 94 pending BPJS claim files for inpatients out of 1427 files that had been submitted for claims to BPJS. This is due to coding errors, incorrect data entry, incomplete supporting examinations such as the absence of therapy and laboratory results. The method used in this research is qualitative with in-depth interviews with the Assistant Manager of Insurance Control and the officer in charge of Inpatient Claims at Mitra Siaga Tegal Hospital. The purpose of this study was to find out the causes of pending claims for hospitalization in September 2022 at Tegal Mitra Siaga Hospital. The results of the study show that pending cases of inpatient BPJS claims at Mitra Siaga Hospital in Tegal can occur due to several factors, which consist of administrative, medical, and coder aspects. The most common factor causing pending hospitalization claims was the coder aspect in 76 cases